Effect of 17β Estradiol on the Economic Parameters of silkworm, Bombyx mori - Magdum V.Β.; Magadum, S.B. (ENTOMOLOGIA HELLENICA, 1992)
The effect of 17-P estradiol on the precocooning and post cocooning parameters of silkworm (Pure Mysore breed) were studied. The 17-β estradiol of 1, 5 and 10 μg/ml concentration was topically applied independently at 36h to III, IV and V instar larvae (Treatment-1), at 48h to IV and V instar larvae (Treatment-2) and at 72h to V instar larvae (Treatment-3). The repeated applications with each concentration of 17-β estradiol in Treatment 1&2 larvae or single application in Treatment 3 variously affected the precocooning and post cocooning parameters. The repeated applications of 1 pg 17-β estradiol (Treatment-1) improve the fecundity and decrease the larval duration, cocooning and moth emergence percentages.